Effect of index contrasts in the wide spectral-range control of slot waveguide dispersion - Ryu, Hyungsuk; Kim, Jaehun; Jhon, Young Min; Lee, Seok; Park, Namkyoo (OPTICAL SOC AMER, 2012)
Here we examine the waveguide dispersion property of slot waveguides, approaching/analyzing the given problem with respect to the normalized index contrast, Delta n(slot-core)/n(core) and Delta n(core-clad)/n(core) between adjacent layers. For two index contrasts of concern, it is found that their contributions to slot waveguide dispersions are substantially different, with Delta n(slot-core) and Delta n(core-clad) each acting preferentially on short-and long-wavelength regions. Additional degrees of freedom in the waveguide design, such as the effect of absolute refractive index and waveguide geometry are also investigated to enable flexible tuning of the waveguide dispersion. Focusing on the unexplored regime of slot waveguides design in short wavelength (<1 mu m), we also study the feasibility of low-threshold super-continuum sources using a Ta2O5/TiO2/silica slot, either of two-octave spectral width ( 0.467-1.581 mu m), or of one-octave, near unity coherence vertical bar g(12)((1))vertical bar = 1. (C) 2012 Optical Society of America
Keywords: SUPERCONTINUUM GENERATION; OPTICAL-PROPERTIES